2014
DOI: 10.1007/s13277-013-1585-2
|View full text |Cite
|
Sign up to set email alerts
|

Early molecular response in chronic myeloid leukemia patients predicts future response status

Abstract: Imatinib is the frontline therapy for chronic myeloid leukemia (CML) management. Most of the CML patients achieve major responses, but a proportion (nearly 25-35%) of them develop drug resistance. Molecular monitoring using quantitative real-time PCR at regular intervals according to European LeukemiaNet (ELN) helps in the assessment of long-term outcomes in imatinib-treated CML patients. Eighty-four CML patient samples (42 at diagnosis and 42 at 3-month intervals from the same patients) were analyzed for Bcr-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Total RNA (1 μg) was reversely transcribed into complementary DNA using high-capacity reverse transcription kit (Applied Biosystems) and used for of BCR-ABL1 fusion transcript types [5,6] and expression analysis. [7] TKD mutations were analyzed in DNA using Sanger sequencing method. [8]…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA (1 μg) was reversely transcribed into complementary DNA using high-capacity reverse transcription kit (Applied Biosystems) and used for of BCR-ABL1 fusion transcript types [5,6] and expression analysis. [7] TKD mutations were analyzed in DNA using Sanger sequencing method. [8]…”
Section: Methodsmentioning
confidence: 99%
“…12 Kagita et al observed their study the optimal response was 100 %, and no suboptimal response. 6 In this study it was observed that mean haemoglobin, total leukocyte count, platelet count, basophil, myelocyte were not statistically significant (p>0.05) when compared between BCR-ABL1 ≤10% (optimal) and BCR-ABL1>10 (warning) groups. However, mean typical cells was significantly higher in BCR-ABL1>10 (warning) group.…”
Section: Discussionmentioning
confidence: 59%
“…Kagita et al found, in their study, the median white cell count as 145 x 10 9 /L with range from 13.8 to 308 x l0 9 /L. 6 Marin et al found the median leukocyte count as 139.5 x 10 9 /L with range from 5.1 to 410.9 x 10 9 /L. 11 In our study the majority (46.7%) patients had platelet count ≤400 x 10 9 /L; the mean was 468.5±211.6 x 10 9 /L with range from 160.0 to 1000.0 x 10 9 /L.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations